Ethical Dilemmas in Sharia-Compliant Buy-Now-Pay-Later (BNPL) Services: A Qualitative Phenomenological Approach - Aan Zulyanto; Marini, Marini (Journal of Social and Humanities, 2023)
This study examines the ethical dilemmas experienced by Muslim consumers in using Buy-Now-Pay-Later (BNPL) services in Indonesia. Using a qualitative phenomenological approach with Interpretative Phenomenological Analysis (IPA), this study explores how Muslim consumers perceive, interpret, and negotiate BNPL usage in relation to Islamic financial principles. Data were collected through semi-structured interviews with fifteen Muslim BNPL users in Bengkulu, Indonesia. The findings reveal four main themes: ethical-religious awareness, rationalization of BNPL usage, the role of financial and Islamic financial literacy, and regulatory-institutional uncertainty. Participants generally recognized potential Sharia concerns, particularly regarding riba, late-payment penalties, and unclear contractual terms. However, many continued to use BNPL because of financial convenience, economic necessity, limited alternatives, and insufficient Islamic financial literacy. The study highlights that BNPL usage among Muslim consumers is not merely a financial practice but also a moral experience shaped by religious values, consumer vulnerability, and institutional guidance. These findings underline the need for transparent, responsible, and genuinely Sharia-compliant BNPL models supported by stronger consumer education and regulatory supervision.